Association of ECG Lead I Sign in Patients of Chronic Obstructive Pulmonary Disease - Anjum, Amin; Khalid, Muhammad Khaqan; Shafiq, Smavia; Mustafa, Tanzeel ur Rehman; Munir, Asvad (Indus Journal of Bioscience Research, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is a progressive respiratory condition linked to airflow limitation and inflammation, affecting millions globally. Despite existing diagnostics, early detection remains difficult. The ECG lead I sign, featuring an isoelectric P wave, has emerged as a potential indicator of COPD severity. This study aims to assess the association between ECG lead I sign and COPD severity among patients in Faisalabad, to aid in timely and accessible diagnosis. Objective: To determine the frequency of ECG Lead I sign based on severity of COPD in local patients of Faisalabad. Duration of Study: Six months following ethical approval. Data Collection: A total of 174 COPD patients aged ≥40 years were enrolled through non-probability consecutive sampling. Patients with prior cardiovascular diseases or asthma were excluded. Data were collected using clinical assessments and ECG testing. COPD severity was classified using GOLD criteria, and the Lead I sign was defined per Schamroth’s criteria. Results: The mean age of participants was 60.36 ± 12.14 years, with 70.1% males. The ECG Lead I sign was present in 29.3% of patients. The highest frequency was noted in very severe (38.9%) and mild (38.2%) COPD cases. Conclusion: This study found the ECG Lead I sign in about one-third of COPD patients, with higher frequency in very severe and mild cases, suggesting a complex link to disease progression. Due to its non-invasive, low-cost nature, it may aid COPD screening where spirometry is lacking. Further multi-center research is needed to confirm its diagnostic and prognostic value.